Future of Technical Vocational Education and Training (TVET) &TVET in Future: (A reference to Post Covid-19) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2025)
TVET-The Technical Vocational Education and Training is getting aligned to meet the changing technologies and the working profiles &workforce skills for disrupting jobs. The requirements of TVET gained importance as a part of Sustainable Development Goals (SDG)2030 of United Nations (UN) with specific reference to SDG-4 (Quality Education), SDG- 8 (Decent Work and Economic Growth), while keeping in view the importance of SDG5(Gender Equality). In Post Covid-19, SDG-13 (Climate Action) got priority again; also, theindustry job profiles changing to less human intervention moving towards automation. SDGs, CoP 21 Paris Climate Conference, and the Sendai Framework for Disaster Risk Reduction2015 were all set to make the world a better living place and align workplace practices to meet the above three crucial global agreements' requirements. The United Nation developed the Medium-Term Strategy (MTS) to examine the strategicdirection and road map to identify priorities. The Medium-Term Strategy 11l of UNESCOUNEVOC set for 2021-2023, setting out TVET institutions' requirements to meet quality skill training for a sustainable future of work. Technology has sustained humanity throughout the Covid pandemic. Technology continues to redefine how the workforce works and how we live, interact and do all activities in this Covid unsafe world. TVET skills help our future work and shape TVET programs to fulfil the education SDG 2030 framework action keeping in mind the key technological trends, ensuring its progressive reach and adaption to its desiredimpacts. Technology is changing the future of work through automation, artificial intelligence, and robotics needed in different occupations and various skills; therefore Government's focus required as policymakers. The budget of Gol sets new directions forgrowth setting Rs. 50,000 Crs. (USD 7000 Mn.) incentivising Research and Skill Development, leading India to be self-sustainable and align with the UN's goals. The TVET development path has to adapt these, leading to a new world of work in India. There won't be abetter time for Reskilling in TVET than the present and make the workforce digitally ready. TVET is imbibing ICT and making processes climate-friendly through green offshoots emerging on the economic front as the critical artefacts of Vocational Education in Future.Indian TVET programs have to benchmark the advanced economies' TVET skill requirements from where India generates foreign remittances because of its demographic strength. The future of TVET has grown brighter, and TVET in the future has to be muchdifferent, aligning the technology requirements of the further years.